REPRESI DAN PERSEKUSI TERHADAP ETNIS ROHINGYA DI MYANMAR DILIHAT DARI PERSPEKTIF HUKUM INTERNASIONAL DAN HAK ASASI MANUSIA - Zai Syahril Nur; Suswoto Suswoto (Universitas Janabadra, 2019)
The Repression and Persecution of Ethnic Rohingnya in Myanmar is a very crucial problem of International Law and Human Rights. Conflict between citizenship and thejurisdiction of state sovereignty is a fundamental polemic of international law and human rights. Repression and persecution on an ethnic group in a country is discriminatory and contrary to International Law and Human Rights. This thesis aims to identify the Repression and Persecution by Myanmar on Rohingnya Ethnic Group and Human Rights protection for Rohingnya Ethnic Group that has been Repressed and Persecuted by Myanmar. Accordingly, this research employed normative juridical methods that emphasized on the rules of law and international agreements and analyzed using prescriptive qualitative method. It can be concluded from the results of research and analysis that the Repression and Persecution on Rohingnya Ethnic Group by Myanmar is a violation of International Law and Human Rights. The State has the sovereignty to regulate and implement its own laws and determine who deserves to be its citizen, which is recognized in International Law. However, the protection of Ethnic groups and the right of citizenship have also been regulated in the instruments of International Law such as the Anti-discrimination Convention and the Citizenship Convention in order to protect human rights. Myanmar is responsible for the Repression and Persecution on Rohingnya Ethnic Group because it is a violation of the norms of jus cogens of International Law and other instruments of human rights. Such Repression and Persecution can be categorized into Crimes Against Humanity, so that the International Criminal Court has a Jurisdiction to adjudicate Myanmar for the Repression and Persecution on Rohingnya Ethnic Group.Keywords : rural areas, university services, human resource improvement, village regulations.